Clinical Profile and Outcome of Esophageal Button Battery Ingestion in Children: An 8-Year Retrospective Case Series - Mustafa Erman Dörterler (Emergency Medicine International)
Objective. To present the clinical profile and outcomes of esophageal button battery ingestion cases treated at our institution over an 8-year period. Methods. A total of 17 children who presented after ingesting a button battery and were treated at a tertiary care clinic over an 8-year period were included in this retrospective case series study. Data on patient demographics and esophageal location of the battery, time from ingestion to admission, symptoms, grade of mucosal injury, size of the battery, management, complications, and follow-up outcome were recorded. Results. Median age was 29 months (range, 2–99 months). Boys comprised (n=11, 64.7%) of the study population. The most common location was the proximal esophagus (n=10, 58.8%). The median time from ingestion to admission was 6 h (range, 3–24 h). Hypersalivation alone (n=6, 35.3%) or together with vomiting (n=5, 29.4%) was the most common symptom. Grade IIA mucosal injury was noted in six (n=6, 35.3%) patients. The diameter of the battery was a median of 18.0 mm (range, 14–22 mm). We did not observe any correlation between the size of the battery and the grade of the injury. Early postoperative complications were encountered in one patient (n=1, 5.8%) and late postoperative complications were noted in eight patients (n=8, 47.1%) which required further esophageal dilatations, and follow-up revealed normal findings in eight patients (n=8, 47.1%) and mortality occurred in one patient. Conclusion. The current case series study describing the clinical profiles and outcomes of 17 children who had ingested an esophageal button battery revealed male predominance, young patient age, and admission after a median of 6 h (3–24 h) of ingestion with nonspecific symptoms. Our findings confirm the success of rigid endoscopy to remove esophageal button batteries and indicate the likelihood of severe complications after removal.